In-Situ Electrolyte for Electrosynthesis: Scalable Anodically-Enabled One-Pot Sequence from Aldehyde to Isoxazol(in)es - Al-Romema, Abdulaziz; Xia, Honglin; Mayrhofer, Karl; Tsogoeva, Svetlana; Nikolaienko, Pavlo (Chemistry - A European Journal, 2024)
Electrochemical transformations are considered a green alternative to classical redox chemistry as it eliminates the necessity for toxic and waste producing redox reagents. Typical electrochemical reactions require the addition of a supporting electrolyte – an ionic compound to facilitate reaction medium conductivity. However, this is often accompanied by an increase in the amount of produced waste. Here, we report an “in-situ electrolyte” concept for facile, transition-metal-free, additive-free one-pot electrochemical preparation of isoxazol(in)es, important scaffolds for biologically active natural and synthetic molecules, from the respective aldehydes. The protocol utilizes no halogenated solvents and no external oxidants, while salt side-products provide the ionic conductivity necessary for the electrosynthesis. The electrolysis is performed in an undivided cell, using the state-of-the-art electrodes for the chlor-alkali industry dimensionally stable and scalable mixed metal oxide anode and platinized titanium cathode of high durability. The cascade transformation comprises the condensation of aldehyde to oxime followed by its anodic oxidation and subsequent intra- and/or intermolecular [3+2] cycloadditions with an appropriate dipolarophile. Chemical yields up to 97 %, and good Faradaic efficiency, scalability, and stability are observed for most substrates in a broad scope.
CRIS-Team Scopus Importer:2024-11-22
Keywords: Cycloaddition; Electrosynthesis; Isoxazole; One-pot; “In-situ electrolyte”

Synthesis and Photo/Radiation Chemical Characterization of a New Redox-Stable Pyridine-Triazole Ligand - Al-Romema, Abdulaziz; Plass, Fabian; Nizovtsev, Alexey; Kahnt, Axel; Tsogoeva, Svetlana (ChemPhysChem, 2024)
Photocatalysis using transition-metal complexes is widely considered the future of effective and affordable clean-air technology. In particular, redox-stable, easily accessible ligands are decisive. Here, we report a straightforward and facile synthesis of a new highly stable 2,6-bis(triazolyl)pyridine ligand, containing a nitrile moiety as a masked anchoring group, using copper(I)-catalyzed azide-alkyne cycloaddition (CuAAC) click reaction. The reported structure mimics the binding motif of uneasy to synthesize ligands. Pulse radiolysis under oxidizing and reducing conditions provided evidence for the high stability of the formed radical cation and radical anion 2,6-di(1,2,3-triazol-1-yl)-pyridine compound, thus indicating the feasibility of utilizing this as a ligand for redox active metal complexes and the sensitization of metal-oxide semiconductors (e. g., TiO2 nanoparticles or nanotubes).
CRIS-Team Scopus Importer:2024-08-02
Keywords: click chemistry; laser photolysis; pulse radiolysis; pyridine-triazole; redox-stable ligand